Pelatihan Kepemimpinan Dasar dalam Membangun Jiwa Kepemimpinan dan Berorganisasi Siswa di SMA Tunas Luhur - Moh. Rofiki; Eka Diana; Muhammad Ainul Yaqin; Fahrudin Fahrudin; Surianto Surianto; Fathor Rohman (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
Leadership and organization are two things that are interrelated and cannot be separated. The absence of basic leadership training is a problem experienced by partners. The participation of Tunas Luhur High School as a partner in this service activity provides a place and human resources to be given training. This basic leadership training service activity is a collaboration of lecturers and students in the Islamic Education Management Study Program at Nurul Jadid University. This activity uses participatory lecture and discussion methods. Training activities are carried out through several noble stages from the observation stage, the preparation stage, the implementation stage and the evaluation stage. The results of the training given to the participants show that this activity has provided new knowledge and is useful for the training participants in facing a competitive and destructive era like today. This is based on the results of evaluations carried out by conducting comparisons and interpretations of the results of the pre-test and post-test carried out before and after the training.